Digestive System and Severe Acute Respiratory Syndrome Coronavirus 2: New Era of Microbiome Study and Gastrointestinal Tract Manifestations during the Coronavirus Disease-19 Pandemic - Kossumov, Alibek; Mussabay, Karakoz; Pepoyan, Astghik; Tsaturyan, Vardan; Sidamonidze, Ketevan; Tsereteli, David; Supiyev, Adil; Kozhakhmetov, Samat; Chulenbayeva, Laura; Dusmagambetov, Marat; Pignatelli, Massimo; Zhumadilov, Zhaxybay; et al. (Open Access Macedonian Journal of Medical Sciences, 2021)
Main focuses of the review were that during the pandemic of SARS-CoV-2 were gastrointestinal disorders were accompanying. Viral RNA and viral particles are found in feces for more than 30 days. Although SARS-CoV-2 primarily causes lung infection through binding to ACE2 receptors, intestinal epithelial cells, especially enterocytes of the small intestine, also express ACE2 receptors. It is also known that a respiratory viral infection causes disturbances in the gut microbiota. Diet, environmental factors, and genetics play an important role in the formation of gut microbiota, which can affect immunity. The diversity of gut microbiota diminishes in old age, and Covid-19 has been mostly fatal in older patients, further indicating the role that gut microbiota may play in this disease. It is therefore plausible that the gut microbiota could be a new therapeutic target and that probiotics could have a role in the management of these patients.